2009
DOI: 10.1007/s00296-009-1125-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TNFα and IL1β in rheumatoid arthritis synovial fibroblasts by leukotriene B4

Abstract: Arachidonic acid metabolites, such as leukotriene B4 (LTB4), are known to play an important role in pathogenesis of rheumatoid arthritis (RA). Apart from leukocytes, RA synovial fibroblasts (RASF) produce a broad array of inflammatory mediators to recruit, retain and activate immune cells and resident mesenchymal cells in the joints to promote ongoing inflammation and tissue destruction. To determine how LTB4 may contribute to this process, RASF was cultured from synovial tissues collected from RA patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
1
24
1
Order By: Relevance
“…Recent study has suggested that LTB4 is an essential and non-redundant role in both acute and chronic inflammation of rheumatoid arthritis [10]. In addition, exogenous LTB4 could increase the expression of cytokines like TNF-α and IL-1β in human synovial fibroblasts [26]. We thus investigated whether LTB4 is involved incytokines release in human synovial fibroblasts.…”
Section: Resultsmentioning
confidence: 96%
“…Recent study has suggested that LTB4 is an essential and non-redundant role in both acute and chronic inflammation of rheumatoid arthritis [10]. In addition, exogenous LTB4 could increase the expression of cytokines like TNF-α and IL-1β in human synovial fibroblasts [26]. We thus investigated whether LTB4 is involved incytokines release in human synovial fibroblasts.…”
Section: Resultsmentioning
confidence: 96%
“…Under various disease states, leukocytes can be activated to locally produce LTs that initiate and amplify the inflammatory process [14,17,19]. For example, LTB 4 binds to BLT1, leading to activation of NF-B inflammatory cascades, generation of cytokines, and production of ROS [33][34][35][36]. Our previous studies have suggested a role for LTs in the development of early stages of DR [20,37].…”
Section: Introductionmentioning
confidence: 99%
“…It is rapidly formed by macrophages, neutrophils, mast cells and dendritic cells and is a powerful chemoattractant for myeloid leukocytes as well as for activated T cells, inducing their migration into inflamed tissue 7. LTB4 is also involved in the differentiation of naïve murine T cells by inhibiting the differentiation of regulatory T cells and promoting Th17 cells,8 and can also augment the cytokine production by activated T cells 9. Thus, LTB4 may have a role in chronic inflammatory processes such as muscle inflammation in PM/DM.…”
Section: Introductionmentioning
confidence: 99%